The eﬀect of adversity quotient, technopreneurial learning, and innovation capabilities to the technopreneurship intention - Lativa Hartiningtyas; Muna, Izzatul (Indonesian Journal of Islamic Economics Research, 2024)
The aim of this research is to determine the influence of the adversity quotient, technopreneurial learning, and innovation capabilities on the technopreneurship intention. Based on research that has been conducted, the independent variables consisting of adversity quotient, technopreneurial learning, and innovation capabilities each have a significant influence on the technopreneurship intention variable as seen from the results of the regression analysis. The results of the classical assumption tests in the form of multicollinearity tests, normality tests and heteroscedasticity tests also show that the data meets the classical assumptions so it can be concluded that there are no multicollinearity, normality and heteroscedasticity.